OPTIMASI PENGAWASAN OLEH OTORITAS JASA KEUANGAN PADA BISNIS ASURANSI DI INDONESIA - BUDI SUTRISNO; I GUSTI AGUNG WISUDAWAN; DIMAN ADE MULADA (SOSIAL SAINS DAN TEKNOLOGI, 2023)
The development of the insurance business in Indonesia is also colored and overshadowed by various problems such as disputes between insurance companies and consumers or customers regarding complicated claims procedures, misunderstandings about the contents of policies, rejection of insurance claims, services provided by insurance companies that are not optimal, customer anger due to Insurance companies fail to pay Insurance Claims and Fraud, namely intentional fraud committed against or by insurance companies or agents, for the purpose of financial gain. Therefore, it is necessary to optimize supervision by OJK on the insurance business in Indonesia. The type of research used in this research is Normative Research with a Statute Approach and a Conceptual Approach. The results of this study are optimizing the OJK's supervision of the Insurance Business in Indonesia, which is a combination of supervisory models, namely direct supervision (active) and indirect supervision (passive) and preventive forms of legal protection, namely creating responsive and progressive regulations governing the insurance business. especially tightening licensing and reporting mechanisms in its supervision and repressive forms of legal protection, namely the OJK in collaboration with law enforcement officers to conduct investigations and investigations into cases of insurance company defaults including providing criminal sanctions (by the Police and the Prosecutor's Office assisted by the OJK). In addition, OJK provides administrative sanctions for insurance companies, namely revocation of insurance company licenses, closing companies and taking profits from insurance companies to pay compensation to their customers